Operational excellence as a means to achieve an enduring capacity to change – revision and evolution of a conceptual model - Carvalho, A. M. (2017)
The efforts to develop a visual framework that depicted the relationships between the concepts of operational excellence, organizational culture and organizational agility concluded with the development of an early conceptual model depicting each concept, their enablers, the links between them and their results. However, as research advanced and theory and discussion cumulated, doubts were generated over the capacity of the model to clearly depict the true nature of some of the relationships between concepts. At the same time, this model seemed to focus too much in each of the concepts and their components, neglecting other factors with possible influence in their relationships. In face of these limitations, a broad revision of the model was performed, with efforts to reinforce its accuracy. In this paper we present the revised version of the model, aiming to offer a broader perspective of the phenomena. In this sense, it keeps its focus on culture, excellence and agility and revises the links between them, but also considers other factors that can influence these relations and their results.